STRATEGI KOMUNIKASI BNN DALAM PROGRAM REMAJA TEMAN SEBAYA ANTI NARKOBA GEN Z DI KOTA BANDA ACEH - Novi Susilawati; Deni Yanuar; Maulidya Rizki (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2023)
The trend of drug abuse in Indonesia is increasing, and one of the areas that have problems with drugs is Banda Aceh. Anti-Drug Peers Youth is a program that is included in the scope of National Priority (PN) activities and is a drug abuse prevention program under the auspices of the BNN main program. The purpose of this studio was to find out how the communication strategy used by the National Narcotics Agency (BNN) of Banda Aceh in campaigning for the Anti-Drug Peer Youth Program for Generation Z in Banda Aceh. The research method used is descriptive qualitative, using interview techniques with three informants. The results of the study show that regardless of the communication strategy implemented by youth they are selected and are seen as active and have been competent. They are considered capable of being activists in compiling messages using simple language that is easily understood by teenagers. The message delivery used is through canalizing and educative methods and uses spoken words and printed writing media.